Islam in South Asia in practice / edited by Barbara D Metcalf (Ranikhet, 2009)
This book brings together the work of more than thirty scholars of Islam and Muslim societies in South Asia to create a rich anthology of primary texts that contributes to a new appreciation of the lived religious and cultural experiences of the world's largest population of Muslims.
Keywords: Islam